APPLICATION OF NEURONAL NETWORKS TO ENHANCE MULTI-ANSWER PROBLEMS TO IMPROVE QUALITY - Cevallos Ampuero, Juan (2004)
This article deals with the application of neuronal networks in multi-answer problems to improve quality. From a conceptual analysis, an application showing the efficiency of neuronal networks using the backpropagation network with training is shown through backpropagation-traingdn.